(untitled) (Ingeniería, Sostenibilidad y Sociedad, 2022)
This project will involve modeling an information system for recording and controlling sales, collecting real data from the Lago Park Restaurant. The restaurant is located in the village of Los Vados, has been in business for seven years, and has great potential for growth and recognition among the residents of Cúcuta. For this reason, improvements are needed in the sales control system to ensure efficient operation.